BUSINESS-ORIENTED COMPUTERS: A FRAME OF REFERENCE. - Boutell, W. S. (The Accounting Review, 1964)
Abstract The modern business-oriented computer is an adaptation, with minor modifications, of the earlier and more general notion of a stored-program, digital computer. Business-oriented computers have been developed largely as a result of a concerted effort on the part of computer manufacturers to develop equipment, which would be suitable to the requirements of business data processing. For the most part, however, accountants have had very little to say about the kind of equipment which has been made available to the business firms. Consequently, each installation has been approached on an ad hoc basis, and there appears to be a wide divergence in accomplishment. Business-oriented computer should be taken as a frame of reference, and instead of superimposing the computer on the business information system of the firm, that the systems designer should build or rebuild the entire system based upon the theoretical concepts inherent in the computer itself. Business-oriented computer becomes an adequate frame of reference for exploring the possibilities and ramifications of a normative business information system for the firm.